VERTICAL TRANSMISSION OF HUMAN IMMUNODEFICIENCY VIRUS (HIV) TYPE 1. MATERNAL PERINATAL INSTITUTE OF LIMA - Velásquez Vásquez, Carlos (2015)
BACKGROUND: AIDS in children less than 15 years is mainly acquired through vertical transmission of human immunodeficiency virus type 1 (HIV). Knowledge on the pathogenesis of this infection has progressively increased, and several therapeutic trials have been proposed to reduce the maternal viral load in order to prevent the vertical transmission of the virus. Zidovudine (AZT) is the drug with most cumulated clinical. The Instituto Materno Perinatal in Lima, Perú, has roughly 24 000 deliveries per year, and is pioneer in using AZT (shorted course) in pregnant women for prevention of vertical transmission of HIV OBJECTIVES: To determine the vertical transmission rate of HIV in our institute, and the impact of the preventive use of AZT. MATERIAL AND METHODS: The study included 113 children of HIV infected mothers, bom and controlled in the period 1998 to 2001. Diagnosis of perinatal infection was basedon the polymerase chain reaction (PCR) test in children older than 6 months, and on the ELISA test in children older than 18 months. RESULTS: The vertical transmission rate in the group treated with AZT was 5,5% and 29,2 % in the untreated group. CONCLUSIONS: There was a protective effect of the antiretroviral therapy (OR: 0, 14, CI95%) with regards to those who were not treated due to delayed postnatal diagnosis. Infection risk decreased from 1/3 to 1/20 in children of mothers treated with AZT.